Carbohydrate-protein coingestion improves multiple-sprint running performance - Highton, J.; Twist, C.; Lamb, K.; Nicholas, C. (Journal of Sports Sciences, 2013)
Acute carbohydrate-protein ingestion has been shown to improve steady-state endurance performance. This study compared the effects of carbohydrate and carbohydrate-protein ingestion on self-regulated simulated multiple-sprint sport performance. Nine participants completed two trials of a modified Loughborough Intermittent Shuttle Test involving 4 x 15 min blocks of regulated exercise followed by 2 x 15 min blocks of self-regulated exercise. Participants consumed 2.5 ml/kg of an 8% carbohydrate (CHO trial) or 6% carbohydrate plus 2% whey protein beverage (CHO-P trial) every 15 minutes. Distance covered (4.2%) and maximal speed (6.1%) decreased (P < 0.05) in the final 15 min of exercise, and whilst not significant, carbohydrate-protein elicited a very likely moderate (2.5: 90% confidence limits; ±1.4%) and possibly small (1.9: ±3.3%) improvement in each variable, respectively. Average running speed declined in the final 15 min of the CHO trial only (P = 0.002), with protein providing a likely small improvement (2.7%: ±2.5%). No differences (P > 0.05) between beverages were observed in body mass or plasma volume change, urine volume, heart rate, gut fullness, rating of perceived exertion (RPE), blood glucose or serum insulin. Blood urea concentration increased in the CHO-P trial only (mean ± SD: 45.4 ± 9.9 c.f. 39.2 ± 11.4 g/dL, P = 0.003). These findings show carbohydrate-protein ingestion is likely to enhance multiple-sprint sport exercise performance above carbohydrate, potentially through altered central fatigue or increased protein oxidation.